Pemanfaatan Pasta Labu Kuning dan Pasta Kacang Hijau dalam Pembuatan Kukis - Apriyanti, Tutik; Fitriani, Shanti; Rahmayuni, (JURNAL AGROINDUSTRI HALAL, 2022)
Cookies are a type of snack that tastes sweet, has a crunchy texture, made from flour with other additives such as eggs, margarine, powdered sugar, and powdered milk. The purposes of this study was to obtain the best ratio of pumpkin and green beans paste in making cookies that meet the quality of SNI 01-2973-2011. The study was conducted using a completely randomized design (CRD) with four treatments and four replications. The treatment in this research was the diference of the ratio between yellow pumpkin paste and green beans paste, namely LK1 (65:5), LK2 (60:10), LK3 (55:15), and LK4 (50:20). The parameters to be observed are moisture, ash, protein, fat, carbohydrate, β-karoten, crude fiber, as well as descriptive and hedonic sensory tests. Data were analyzed using analysis of variance (ANOVA) and then continued with Duncan’s multiple range test (DMRT) at 5% level. The result showed that the ratio of yellow pumpkin paste and green beans paste significantly affected moisture, ash, protein, fat, carbohydrate, crude fiber, β-karoten, as well descriptive and hedonic sensory tests. The ratio of yellow pumpkin paste amd green beans paste (65:5) was chosen as the best treatment which had 3.26% protein, 5.79% moisture, 2.15% ash, 17.84% fat, 71.97% carbohydrate, 2.19% crude fiber, and 17.53 µg/g β-karoten with a description of yellow, pumpkin yellow flavored, slightly crunchy texture, and yellow pumpkin taste. Hedonic assessment of color, aroma, cruncy texture, taste, and overall assessment were liked by panelists.